The influence of dividend policy, profitability, and capital structure on firm value - Syahara, Carissa Citra Aulia; Nursiam, Nursiam (Indonesia Auditing Research Journal, 2024)
This research seeks to determine and analyze the impact of dividend policy, profitability, and capital structure on company value, focusing on LO45 companies listed on the Indonesia Stock Exchange from 2020 to 2022. Using a purposive sampling method, 27 companies met the predetermined criteria, resulting in a sample size of 81. The secondary data for this research was obtained from annual and sustainability reports published by the companies on the website www.ids.co.id. The results indicate that dividend policy and profitability significantly influence company value, while capital structure does not.